2015
DOI: 10.3892/ijo.2015.2917
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist (IL1RN) is associated with suppression of early carcinogenic events in human oral malignancies

Abstract: Inflammatory abnormalities have been implicated in the pathogenesis of various human diseases, including cancer. Interleukin-1 receptor antagonist (IL1RN) is a potent anti-inflammatory molecule that modulates the biological activity of the proinflammatory cytokine, interleukin-1. The aim of this study was to examine the expression of IL1RN in oral squamous cell carcinomas (OSCCs), and to determine its clinical significance. Expression levels of IL1RN in matched normal and tumor specimens from 39 OSCCs were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…IL1RN could reduce tumor growth and invasiveness by suppressing IL‐1‐related activities. Previous studies indicated that IL1RN expression was significantly reduced in OSCC tissues as assessed by quantitative real‐time PCR and immunohistochemistry (Lallemant et al, ; Shiiba et al, ). Consistent with these clinical observations, our findings suggested that IL1RN expression was also downregulated in the saliva of OSCC patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IL1RN could reduce tumor growth and invasiveness by suppressing IL‐1‐related activities. Previous studies indicated that IL1RN expression was significantly reduced in OSCC tissues as assessed by quantitative real‐time PCR and immunohistochemistry (Lallemant et al, ; Shiiba et al, ). Consistent with these clinical observations, our findings suggested that IL1RN expression was also downregulated in the saliva of OSCC patients.…”
Section: Discussionmentioning
confidence: 97%
“…Then, solute carrier family 3 member 2 (SLC3A2), S100 calcium‐binding protein A2 (S100A2), and interleukin‐1 receptor antagonist protein (IL1RN) were selected and further prevalidated using enzyme‐linked immunosorbent assay (ELISA) in the three groups. Previous studies have reported the abnormal expression of these three proteins in OSCC tissue samples (Kumar et al, ; Shiiba et al, ; Toyoda et al, ). However, those studies were not based on biomarker detection from saliva samples.…”
Section: Introductionmentioning
confidence: 91%
“…We selected four candidate SNPs in the IL1RN gene from the database of SNPs and previously published polymorphisms associated with cancers [16, 19]. Each SNP had a minor allele frequency >5% in the global population from the 1000 Genomes Project (http://www.internationalgenome.org/).…”
Section: Methodsmentioning
confidence: 99%
“…IL1RN is a natural antagonist of IL-1 and modulates a variety of IL-1-related immune and inflammatory responses. So far, studies of variants in ­ IL1RN in individuals have shown that IL1RN polymorphisms are involved in an increased risk of pulmonary tuberculosis [15], oral malignancy [16], and gastric cancer [14]. Researchers also reported that IL1RN variants are associated with the risk of breast cancer in the female population of South Korea, India, and China [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…The balance between IL1RN and IL-1 plays a crucial role in many diseases, including cancer [10]. IL1RN has been studied in several cancers, including prostate carcinoma [11][12], cervical carcinoma [13], gastric carcinoma [14], bronchogenic carcinoma [15], endometrial cancer [16], lung cancer [17], ovarian cancer [18], oral malignancies [19], leukemia [20], and other cancers.…”
Section: Introductionmentioning
confidence: 99%